Comparison of Blood Pressure in Hypertensive Patients with Monotherapy and Combination Antihypertensive Therapy - Ramadhani, Novely Dwita; Utami, Primanitha Ria; Octavia, Devi Ristian; Desiani, Ekanita (Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR); Vol 3 (2023): Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR)DO - 10.18860/planar.v3i0.2476, 2023)
Background: Hypertension is a cardiovascular risk factor that is closely related to the patient's systolic and diastolic blood pressure profile. Objective: This study aims to determine the comparison of systolic and diastolic blood pressure profiles using antihypertensives in patients with cardiovascular risk factors. Method: Conducted in the period August-December 2021 on 83 patients who met the inclusion criteria, namely outpatients diagnosed with hypertension with cardiovascular risk factors, adult patients over 18 years of age, a medical record sheet, and a written prescription in full. Data analysis used the Kruskal Wallis test. Results: Shows a p value of 0.02 < 0.05 that there is a difference in systolic and diastolic blood pressure when using antihypertensive monotherapy or combination. The use of antihypertensive monotherapy is able to achieve the target of reducing systolic and diastolic blood pressure, namely amlodipine by -42.4mmHg/-11.7mmHg. Meanwhile, the combination antihypertensive that provides maximum results is a combination of 2 drugs, namely Candesartan + Hydrochlorthiazide which produces a reduction of -42.64 mmHg/-16.09 mmHg; a combination of 3 drugs: Amlodipine + Candesartan + Hydrochlorthiazide resulted in a reduction of -49 mmHg/-19.1 mmHg. Conclusion: There are differences in the profile of reducing systolic and diastolic blood pressure when using monotherapy and combination antihypertensives. The choice of monotherapy and combination can provide benefits in reducing blood pressure, tolerability and the level of compliance with the drugs consumed. Rational dose selection and drug selection in hypertensive patients is an important part in achieving successful therapy and preventing drug related problems, so pharmacists need to always monitoring blood pressure profiles as a form of monitoring the effectiveness of existing antihypertensive drugs consumed by patients.